2021
DOI: 10.1007/s13238-021-00837-8
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear m6A reader YTHDC1 regulates the scaffold function of LINE1 RNA in mouse ESCs and early embryos

Abstract: N6-methyladenosine (m6A) on chromosome-associated regulatory RNAs (carRNAs), including repeat RNAs, plays important roles in tuning the chromatin state and transcription, but the intrinsic mechanism remains unclear. Here, we report that YTHDC1 plays indispensable roles in the self-renewal and differentiation potency of mouse embryonic stem cells (ESCs), which highly depends on the m6A-binding ability. Ythdc1 is required for sufficient rRNA synthesis and repression of the 2-cell (2C) transcriptional program in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 50 publications
8
73
0
Order By: Relevance
“…This manner of transcript inhibition can be used by mouse embryonic cells to repress LINE1 and other retrotransposons (IAP, ERVK, etc.) [161,162]. A lack of YTHDC1, a factor that initiates silencing by recognizing N6-methyladenosine modification and transcript binding, leads to the transition to the 2-cell embryo stage [161,162].…”
Section: Regulation Of L1 In the Early Stages Of Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This manner of transcript inhibition can be used by mouse embryonic cells to repress LINE1 and other retrotransposons (IAP, ERVK, etc.) [161,162]. A lack of YTHDC1, a factor that initiates silencing by recognizing N6-methyladenosine modification and transcript binding, leads to the transition to the 2-cell embryo stage [161,162].…”
Section: Regulation Of L1 In the Early Stages Of Embryogenesismentioning
confidence: 99%
“…[161,162]. A lack of YTHDC1, a factor that initiates silencing by recognizing N6-methyladenosine modification and transcript binding, leads to the transition to the 2-cell embryo stage [161,162]. Post-transcriptional degradation of L1 in early embryos can occur due to the nuclear exosome targeting (NEXT) complex, the central factor of which is Zcchc8 [131].…”
Section: Regulation Of L1 In the Early Stages Of Embryogenesismentioning
confidence: 99%
“…In the absence of YTHDC1, m6A-marked LINE1 was recruited on the Dux1 locus where it mediated chromatin repression [ 80 ]. These findings were confirmed in a follow up study by Chen et al, who found that m6A-marked LINE1 can complex with Nucleolin (NCL) to inhibit the re-expression of TE, controlling the execution of the 2C-like state program [ 81 ] ( Figure 1 C).…”
Section: Transposable Elements Rna Modifications and Chromatin Organi...mentioning
confidence: 57%
“…Three studies have recently reported the regulatory activity of m6A over LINE1 in mouse ES cells [ 79 , 80 , 81 ]. The first study [ 79 ], which looked at genome-wide regulation of chromatin accessibility by m6A ( Figure 1 A), found the robust enrichment of m6A at chromatin-associated repetitive RNAs (carRNAs) of the mESc genome.…”
Section: Transposable Elements Rna Modifications and Chromatin Organi...mentioning
confidence: 99%
“…These highthroughput experimental data provide a special opportunity for us to explore the interactions between transposon-derived RNAs and chromatin for the understanding of the potential trans-regulatory function of these transposon RNAs. Researchers initiated to utilize the RNA-chromatin interaction data for the discovery that transposon RNAs modulate the process of heterochromatin organization (Hao et al 2020;Chen et al 2021;Liu et al 2021). In this study, we performed a high-throughput proximity MARGI experiment in E14 cells and interpreted the roles of transposon RNAs from the perspective of RNA trans-regulation on gene transcription in embryonic stem cells (ESCs).…”
Section: Introductionmentioning
confidence: 99%